Nutritional determinants as potential contributors to anemia in children and adolescents with malaria by P. vivax - Cabral, Bianca da Conceição; Dias, Rosa Maria; Vieira, José Luiz Fernandes; Moura, Fernanda Maria Lima; de Andrade, Marcieni Ataide (Revista de Epidemiologia e Controle de Infecção, 2021)
Background and Objective: Nutrition, in addition to its physiological function, plays an important role in the recovery of individuals with malaria, a disease that still represents a serious public health problem in the world. The objective of this article is to evaluate the frequency of food intake and the occurrence of anemia in children and adolescent with vivax malaria. Methods: A cross-sectional analytical study was carried out between 2014 and 2015 in the Marajo island. The hemoglobin level was measured by the colorimetric enzymatic reaction and a questionnaire of food intake frequency was used to assess the consumption of foods. Results: A total of 67 patients met the criteria for the inclusion in the study, of which 62.7% were children. There is a high consumption of ultra-processed foods in both age groups. Anemia occurred in 52.2% of patients, and in most of them, it was moderate. There was no significant association between gender, age range, parasitemia at admission with anemia, but a significant association was found between anemia and the ingestion of ultra-processed foods. Conclusion: The ingestion of ultra-processed foods contributes to anemia in children and adolescent with malaria.